2015
DOI: 10.1371/journal.pntd.0004003
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster-Randomized Controlled Intervention Study to Assess the Effect of a Contact Intervention in Reducing Leprosy-Related Stigma in Indonesia

Abstract: BackgroundCan deliberate interaction between the public and persons affected by leprosy reduce stigmatization? The study described in this paper hypothesises that it can and assesses the effectiveness of a ‘contact intervention’.Methods/Principal FindingsThis cluster-randomized controlled intervention study is part of the Stigma Assessment and Reduction of Impact (SARI) project conducted in Cirebon District, Indonesia. Testimonies, participatory videos and comics given or made by people affected by leprosy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 56 publications
2
67
1
1
Order By: Relevance
“…In general, the effectiveness evaluation of interventions is considerably restricted. Only 9 studies applied standardized measures . Those incorporated stigma‐related attitudes and behaviours assessed from the perspective of the patients or the general public.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the effectiveness evaluation of interventions is considerably restricted. Only 9 studies applied standardized measures . Those incorporated stigma‐related attitudes and behaviours assessed from the perspective of the patients or the general public.…”
Section: Resultsmentioning
confidence: 99%
“…While both approaches indicated positive results, the participatory strategy seemed to be superior to the information‐based strategy. Further studies, establishing contact of patients and the general public, indicated positive results . To address self‐stigma, different studies assessed the effect of skills building and counselling for patients, mainly on group level.…”
Section: Resultsmentioning
confidence: 99%
“…Lusli et al [16,17] showed the benefit of psychosocial support like counselling on the leprosy-related stigma. Moreover, Peters et al [18,19] illustrated the success of a contact intervention in Indonesia to reduce leprosy-related stigma in the community. These interventions are likely to work for CL as well.…”
Section: Discussionmentioning
confidence: 99%
“…The SARI project aimed to assess the effectiveness of three stigma-reduction interventions in persons affected by leprosy in Cirebon District, West-Java, Indonesia: counselling, contact [35] and Social Economic Development (SED). The SARI project is a cluster-randomized controlled intervention study and uses the Interactive Learning and Action approach [36] as a guiding methodology.…”
Section: Methodsmentioning
confidence: 99%